Competitive Economic Development of The Republic of Moldova - Perchinschi Natalia; Gribincea Alexandr (International Business and Accounting Research Journal, 2018)
With this general framework in mind, this section has explained through various examples the circumstances in which economic theory would justify a temporary increase in trade barriers – even above the level of commitments in a trade agreement. These circumstances include when an import surge provides an argument for an increase in trade barriers as well as when a change in demand or supply or in policy leads to a sharp contraction for a particular sector and this, in turn, has a negative externality (like in the case of the one-company town). Another argument for trade policy intervention is when something alters the degree of competition in the market – for example, if a company indulges in predatory dumping. Other circumstances include developing countries providing support to infant industry, action to address balance of payment crises, and responding to a sharp increase in the world price of a product. In all these cases, the adoption of restrictive trade policy can be justified as a second-best option.